Mechanisms Involved in the Anti-inflammatory and Vascular Effects of Iberis amara Extract - Khayyal, Mohamed T.; Agha, Azza M.; Zaki, Hala F.; El-Sahar, Ayman; Abdel-Aziz, Heba (Planta Medica, 2015)
The anti-inflammatory potential and vasoprotective effects of an Iberis amara extract in a rat model of arthritis were investigated. I. amara, or bitter candytuft, has long been known for its anti-inflammatory properties on account of its active constituents, including cucurbitacins, kaempferol, and sinapic acid. The present study was intended to explore more in depth its anti-inflammatory activity in both acute (carrageenan rat paw edema) and chronic (adjuvant-induced arthritis) models of inflammation. An extract of I. amara dose-dependently reduced the extent of edema in both models. In the chronic model, this was associated with a reduction in the inflammation mediators tumor necrosis factor-α, interleukin-1β, and prostaglandin E2 and in the antioxidant biomarkers malondialdehyde and total nitrate/nitrite. Because arthritis was reported both clinically and experimentally to contribute towards different vascular complications, it was of interest to study ex vivo the sensitivity of aortic rings in our experimental setup towards norepinephrine, acetylcholine, and sodium nitroprusside. The aortic rings from arthritic rats showed no change in sensitivity to norepinephrine, but showed a reduced sensitivity to sodium nitroprusside and acetylcholine. To show whether the treatment of the arthritis would restore endothelial function, I. amara extract was shown to markedly reduce the reactivity to norepinephrine, but not to appreciably affect the reactivity towards sodium nitroprusside and it had a tendency towards normalizing reactivity to acetylcholine. Taken collectively, the findings imply an improvement in endothelial function and lend support to the use of the extract in rheumatic inflammatory conditions to help safeguard the integrity of the endothelium and reduce the risk of vascular complications.
Keywords: Iberis amara; Brassicaceae; adjuvant induced arthritis; vascular reactivity; inflammation